PEMANFAATAN MEDIA THINGLINK UNTUK MENGEMBANGKAN LITERASI SAINS SISWA DALAM PEMBELAJARAN IPA SAAT PANDEMI DI MTs N 34 - Dwi Ning Wahyuni Budi (Wawasan: Jurnal Kediklatan Balai Diklat Keagamaan Jakarta, 2021)
This study aimed to determine the use of thinglink media for the development of scientific literacy in science learning during the pandemic. This type of research is a classroom action research with a qualitative descriptive method. The data obtained show that 29 students of grade 7.3 can understand scientific literacy with moderate and high qualifications of 40%. The understanding of scientific literacy in this qualification is in the aspect of students' abilities in a personal context and scientific attitudes in support of inquiry activities. Meanwhile, students' abilities in evaluating and designing scientific investigations and interpreting scientific evidence and data are still in low qualification (60%). The ratio of values in cycles 1 and 2 is 40%: 51%. The selection of the right measuring instrument to be embedded in the thinglink media dramatically affects the learning process and measures students' understanding of scientific literacy during the pandemic.